High Diversity and Functional Complementation of Alimentary Canal Microbiota Ensure Small Brown Planthopper to Adapt Different Biogeographic Environments - Liu, Wenwen; Zhang, Xiaowan; Wu, Nan; Ren, Yingdang; Wang, Xifeng (Frontiers in Microbiology, 2020)
Almost all insects harbor commensal bacteria in the alimentary canal lumen or within cells and often play a pivotal role in their host’s development, evolution and environmental adaptation. However, little is known about the alimentary canal microbiota and their functions in sap-sucking insect pests of crops, which can damage plants by removing plant sap and by transmitting various plant viruses, especially in the small brown planthopper, Laodelphax striatellus. In this study, we characterized the alimentary canal microbiota of L. striatellus collected from seven regions in China by sequencing 16S rDNA. The insects harbored a rich diversity of microbes, mainly consisted of bacteria from phyla Proteobacteria, Actinobacteria, Firmicutes, Bacteroidetes and Tenericutes. The composition and abundance of microbiota were more similar as the geographic distance decreased between the populations and clustered by geographic location into three groups: temperate, subtropical and tropical populations. Although the abundance and species of microbes differed among the populations, the various major microbes for each population performed similar functions based on a COG analysis. Greater diversity in ecological factors in different regions might lead to higher microbial diversity, thus enabling L. striatellus to adapt or tolerate various extreme environments to avoid the cost of long-distance migration. Moreover, the abundance of various metabolic functions in the Kaifeng populations might contribute to higher fecundity in L. striatellus.